Fiscal and monetary policy rules in an unstable economy - Soon Ryoo; Peter Skott (University of Massachusetts, Department of Economics, 2015)
This paper examines the implications of different monetary and fiscal policy rules in an economy characterized by Harrodian instability. We show that (i) a monetary rule along Taylor lines can be stabilizing for low debt ratios but becomes de-stabilizing if the debt ratio exceeds a certain threshold, (ii) a 'Keynesian' fiscal policy rule can stabilize the economy at full employment, (iii) a fiscal 'austerity' rule that links fiscal parameters to deviations from a target debt ratio fails to adjust the `warranted' to the 'natural' growth rate and destabilizes the warranted path, (iv) instability may arise from a combination of fiscal and monetary policy rules which separately would stabilize the system, and (v) austerity rules can in some circumstances enhance the stabilizing effects of monetary policy.
Keywords: E12; E52; E62; E63; 330; functional finance; fiscal policy rule; austerity; public debt; Harrodian instability